2013
DOI: 10.5603/kp.2013.0224
|View full text |Cite
|
Sign up to set email alerts
|

Ablation of atrioventricular nodal reentrant tachycardia: predictors of long-term success

Abstract: Typical jump and complete SP elimination are associated with a better outcome. A 2-electrode approach is as effective as > 2 electrode approach. The electrophysiological profile of patients in whom complete SP elimination was achieved may differ from that of patients in whom only SP modification was possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 13 publications
0
9
1
Order By: Relevance
“…Thus, when during the course of ablation procedure a SP modification is achieved, it is worth attempting to perform additional RF applications in order to achieve complete SP ablation, especially in patients with a large echo window (6,8) or in whom the AV nodal refractory period is only slightly prolonged following ablation (5). On the other hand, acute failure is associated with a significantly higher recurrence rate, although not all patients with AVNRT still inducible after ablation suffer from recurrences during (10).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, when during the course of ablation procedure a SP modification is achieved, it is worth attempting to perform additional RF applications in order to achieve complete SP ablation, especially in patients with a large echo window (6,8) or in whom the AV nodal refractory period is only slightly prolonged following ablation (5). On the other hand, acute failure is associated with a significantly higher recurrence rate, although not all patients with AVNRT still inducible after ablation suffer from recurrences during (10).…”
Section: Discussionmentioning
confidence: 99%
“…The diagnosis of AVNRT was based on the presence of AH jump and echo initiating tachycardia during programmed atrial stimulation and/or during incremental atrial pacing close to the Wenckebach point. Typical AVNRT was diagnosed when the earliest retrograde atrial activation during tachycardia was <70 ms from the ventricular activation and was concentric (recorded from coronary sinus), matching that during RV pacing [ 8 , 9 ].Typical jump was defined as a sudden prolongation of AH interval >50 ms with a decrease of 10 ms of S1–S2 interval during programmed atrial pacing [ 5 , 10 ]. Patients were excluded if there were more than one jump (multiple AH jumps) or no AH jump at all.…”
Section: Methodsmentioning
confidence: 99%
“…Although SP modification has already been accepted as a reliable end-point of successful AVNRT ablation [ 3 , 4 ], some studies have shown that in the long-term observation, the recurrence rate was higher in patients with only modification of SP [ 5 , 6 ]. It could be due to the incomplete radiofrequency injury in SP modification that the conduction over SP may resume in months or years [ 5 ]. Therefore it was strongly suggested that complete SP elimination should be the preferred ablation end-point.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Paroxysmal atrioventricular nodal re-entrant tachycardia (AVNRT) is a common supraventricular tachycardia (SVT) which impairs patients' quality of life [1,2] . Usually it is self-limiting, but it may be successfully terminated with vagal manoeuvres or pharmacological agents.…”
Section: Introductionmentioning
confidence: 99%